2021
DOI: 10.1080/03007995.2021.1982684
|View full text |Cite
|
Sign up to set email alerts
|

The burden of undertreatment and non-treatment among patients with non-valvular atrial fibrillation and elevated stroke risk: a systematic review

Abstract: Objective: Global treatment guidelines recommend treatment with oral anticoagulants (OACs) for patients with non-valvular atrial fibrillation (NVAF) and an elevated stroke risk. However, not all patients with NVAF and an elevated stroke risk receive guideline-recommended therapy. A literature review and synthesis of observational studies were undertaken to identify the body of evidence on untreated and undertreated NVAF and the association with clinical and economic outcomes. Methods: An extensive search (1/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…However, OAC undertreatment remains a concern in AF patients, 8 9 being also associated with worse outcomes, 10 especially in high-risk patients. Indeed, with the progressive aging of the AF population, a significant proportion of patients are burdened by concomitant comorbidities and conditions that increase both thromboembolic and bleeding risks, entailing the so-called “clinical complexity” that influences treatment choices and poses significant challenges in the management of AF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, OAC undertreatment remains a concern in AF patients, 8 9 being also associated with worse outcomes, 10 especially in high-risk patients. Indeed, with the progressive aging of the AF population, a significant proportion of patients are burdened by concomitant comorbidities and conditions that increase both thromboembolic and bleeding risks, entailing the so-called “clinical complexity” that influences treatment choices and poses significant challenges in the management of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction, the non-vitamin K antagonist OACs (NOACs; also referred to as direct OACs) represented a safer and effective alternative to vitamin K antagonist (VKA) for stroke prevention in AF patients, 3 and this was reflected by the increasing uptake of NOACs in clinical practice. [4][5][6][7] However, OAC undertreatment remains a concern in AF patients, 8,9 being also associated with worse outcomes, 10 especially in high-risk patients. Indeed, with the progressive aging of the AF population, a significant proportion of patients are burdened by concomitant comorbidities and conditions that increase both thromboembolic and bleeding risks, entailing the so-called "clinical complexity" that influences treatment choices and poses significant challenges in the management of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, DOAC adoption trends are quite variable, with slow integration into clinical practice reported in most countries[ 98 ]. A systematic literature review indicates that suboptimal OACs use is a persisting challenge, despite the availability of DOACs[ 100 ]. After the launch of the first DOAC in 2011, the proportion of DOACs as OAC increased from 3% in 2012 to 42% in 2016 ( P < 0.0001 for the trend)[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with other studies, showing that a total varying from 21.9% to 30.2% did not receive any prophylactic antithrombotic therapy[ 46 , 60 , 70 , 75 , 90 ] with substantial variations across countries. A recent meta-analysis reviewed a total of 11,231 publications, demonstrating in patients with high stroke risk a rate of non-treatment of 23.3% (7.9%-51.1%)[ 100 ]. Undertreatment is frequent in female and older patients, notwithstanding their great stroke risk[ 36 , 87 , 93 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Although anticoagulation is strongly recommended in all major AF guidelines, [3][4][5] physician practices vary widely, and some studies suggest the rate of nontreatment in the United States, both for hospitalized or ambulatory patients, may be as high as 50% in patients with elevated stroke risk. [23][24][25] It is estimated that 50,000 preventable strokes per year occur in the United States related to suboptimal anticoagulation care for AF. 26 A recent Canadian study showed that initiation of oral anticoagulation in the ED is associated with higher long-term use than when prescription is deferred to outpatient care following discharge.…”
Section: U-care Af Pathway: Anticoagulationmentioning
confidence: 99%